A Compartmentalized Reduction in Membrane-Proximal Calmodulin Reduces the Immune Surveillance Capabilities of CD8+ T Cells in Head and Neck Cancer - Chimote, Ameet A.; Gawali, Vaibhavkumar S.; Newton, Hannah S.; Wise-Draper, Trisha M.; Conforti, Laura (Frontiers in Pharmacology, 2020)
The limited ability of cytotoxic CD8+ T cells to infiltrate solid tumors and function within the tumor microenvironment presents a major roadblock to effective immunotherapy. Ion channels and Ca2+-dependent signaling events control the activity of T cells and are implicated in the failure of immune surveillance in cancer. Reduced KCa3.1 channel activity mediates the heightened inhibitory effect of adenosine on the chemotaxis of circulating T cells from head and neck squamous cell carcinoma (HNSCC) patients. Herein, we conducted experiments that elucidate the mechanisms of KCa3.1 dysfunction and impaired chemotaxis in HNSCC CD8+ T cells. The Ca2+ sensor calmodulin (CaM) controls multiple cellular functions including KCa3.1 activation. Our data showed that CaM expression is lower in HNSCC than healthy donor (HD) T cells. This reduction was due to an intrinsic decrease in the genes encoding CaM combined to the failure of HNSCC T cells to upregulate CaM upon activation. Furthermore, the reduction in CaM was confined to the plasma membrane and resulted in decreased CaM-KCa3.1 association and KCa3.1 activity (which was rescued by the delivery of CaM). IFN production, also Ca2+- and CaM-dependent, was instead not reduced in HNSCC T cells, which maintained intact cytoplasmic CaM and Ca2+ fluxing ability. Knockdown of CaM in HD T cells decreased KCa3.1 activity, but not IFN production, and reduced their chemotaxis in the presence of adenosine, thus recapitulating HNSCC T cell dysfunction. Activation of KCa3.1 with 1-EBIO restored the ability of CaM knockdown HD T cells to chemotax in the presence of adenosine. Additionally, 1-EBIO enhanced INF production. Our data showed a localized downregulation of membrane-proximal CaM that suppressed KCa3.1 activity in HNSCC circulating T cells and limited their ability to infiltrate adenosine-rich tumor-like microenvironments. Furthermore, they indicate that KCa3.1 activators could be used as positive CD8+ T cell modulators in cancers.